2015
DOI: 10.1101/gr.190124.115
|View full text |Cite
|
Sign up to set email alerts
|

Enabling functional genomics with genome engineering

Abstract: Advances in genome engineering technologies have made the precise control over genome sequence and regulation possible across a variety of disciplines. These tools can expand our understanding of fundamental biological processes and create new opportunities for therapeutic designs. The rapid evolution of these methods has also catalyzed a new era of genomics that includes multiple approaches to functionally characterize and manipulate the regulation of genomic information. Here, we review the recent advances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 278 publications
(310 reference statements)
0
61
0
Order By: Relevance
“…Targeting efficiency of CRISPERCas9 is more than ZFNs and TALENs [1]. It was reported that targeting efficiency of TALENs and ZFNs in human cells lie from 1% to 50% [29][30][31].…”
Section: Targeting Efficiency and Of Incidence Of Off-target Mutationmentioning
confidence: 98%
See 1 more Smart Citation
“…Targeting efficiency of CRISPERCas9 is more than ZFNs and TALENs [1]. It was reported that targeting efficiency of TALENs and ZFNs in human cells lie from 1% to 50% [29][30][31].…”
Section: Targeting Efficiency and Of Incidence Of Off-target Mutationmentioning
confidence: 98%
“…This innovating molecular technique enables addition, deletion and substitution of bases by incorporating detectable changes in the DNA of an organism [1]. In comparison with classical genetic engineering which is the cleavage and random insertion of a foreign gene or DNA sequence from a different specie to another.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the genetic syndromes arise from point mutations, modern techniques for correcting point mutation are not efficient and normally induce random insertions and deletions at a target locus subsequent to cellular response to dsDNA breaks (Hilton and Gersbach 2015). However, the development of "base-editing" technique allows the direct, stable transformation of target DNA base into an alternative in a programmable way, without DNA double strand cleavage or a donor template (Komor et al, 2016).…”
Section: Base Editingmentioning
confidence: 99%
“…In addition, targeted nucleases may be used to produce additional sequence-specific genetic and epigenetic outcomes that may be exploited to gain knowledge of genome function and produce desirable alterations. 11 Each of the targeted nucleases described below contains 2 major functional moieties, the first of which is specific DNA recognition. The various platforms differ based on the biochemical nature of the recognition (by protein or RNA), by the modularity of recognition (whether 1, 2, or more components are involved), the size of the recognition domain (and its attendant challenges to cellular delivery), the ease with which the interaction may be engineered to recognize a variety of target sequences, and the specificity of such recognition.…”
Section: Introductionmentioning
confidence: 99%